Problems in Marketing. - Moutinho, Luiz A. M. (Sage Publications, 2007)
. Fully revised and updated, Problems in Marketing includes over 50 new problems. This varied and challenging collection of problems has been written as a learning aid to any marketing textbook. The problems cover a wide range of marketing practice, each problem concentrating on a single concept or technique of marketing management. Problems begin with a full introduction to the concept followed by explicit instructions for solving them. This leads directly to a series of discussion questions to further enhance the application of each problem. Solutions are also available to lecturers by click.